Diagnosing early cognitive decline - when, how and for whom? - Allan, C; Behrman, S; Ebmeier, K; Valkanova, V (Elsevier, 2016)
Mild cognitive impairment (MCI) is a term to describe cognitive impairment in one or more cognitive domains that is greater than any expected age related changes, but not of the magnitude to warrant a diagnosis of dementia. This review considers how early cognitive decline is diagnosed, focusing on the use of neuropsychological tests and neuroimaging, as well as the differential diagnosis. Potential treatments, including secondary prevention, post-diagnostic support and self-help are discussed. Finally, medico-legal matters such as driving, lasting power of attorney and employment are outlined.